The Role of the Duty of Fair Representation in Union Grievance Decisions - Knight, Thomas (Relations industrielles / Industrial Relations, 1987)
This article reports the results of a survey of union staff representatives regarding the impact of the duty of fair representation on grievance handling. The survey confirmed previous research results suggesting that fair representation complaints are frequently reflective of political factionalism within unions or a measure of economic decisions adversely affecting individuals rather than a sign of inadequate representation by unions. It was also found that grievors' exploitation ofthe doctrine does at times cause unions to process unmeritorious grievances, increasing the cost of contract administration to ail parties.